Ovarian teratoma leading to colonic intussusception: a case report - Qiu, Xiujuan; Gao, Jiahao; Gao, Jun (Frontiers in Oncology, 2025)
Intussusception in adults is relatively rare compared to that in children and is typically caused by underlying benign or malignant intestinal diseases. We report a case of a 40-year-old female who presented with colonic intussusception and obstruction caused by an ovarian teratoma invading a segment of the colon. Contrast-enhanced CT imaging revealed a soft tissue mass within the colon, and colonoscopy identified a large cystic lesion approximately 6.0 × 6.0 cm in size located 20 cm from the anal verge. This lesion obstructed the lumen, causing significant narrowing. Preoperatively, the condition was misdiagnosed as intussusception caused by a colonic diverticulum. During laparoscopic exploration, a left ovarian tumor invading the colon was identified as the cause of the intussusception and obstruction. Consequently, partial colectomy and left oophorectomy were performed. Histopathological examination confirmed the diagnosis of a mature ovarian teratoma. The postoperative recovery was uneventful, and the patient was discharged in good health. This case report presents a rare instance of intussusception, highlighting the challenges associated with achieving an accurate preoperative diagnosis. Surgical intervention remains the primary treatment modality for patients with this condition.